Building Brand Equity Through Sustainable and Experiential Marketing - Omar Hasan Ahmed; Nadia Tareq Ahmed; Samer Adel Abd Hussein; Sabah Abdul Wahhab Abdul Razaaq Al-Nuiami; Faris Abdul Kareem Khazal (Environment and Social Psychology, 2026)
The article addresses the linkage between sustainable branding and experiential marketing and how they can be utilized to influence brand equity in consumers today. Even though the previous studies have isolated the strategies separately, there has been minimal empirical evidence to indicate the integration of the strategies and how they will impact on the loyalty, advocacy and the brand trust. The research design will be mixed research design; that is, the researcher will utilize both survey research data (1,200 consumers) and 25 in-depth interviews to determine the independent and interactive impact. Hierarchy regression and interaction models reveal that the effects of sustainability practices and experiential marketing on the brand equity are positive; more so, a combination of the two has a significant impact as compared to each of the two. The final customer loyalty, Net Promoter Scores, and trust was achieved through sustainable brands as a part of the immersive consumer experiences. The further expectations of qualitative sentiment analysis are that experiential interfaces can render sustainability initiatives more legitimate and emotionally connected, and the level of skepticism is not so high concerning greenwashing. The study will be an addition to the theory of brand equity as well as the existing sustainability and experiential marketing theories because it empirically models the connection between sustainable branding and experiential engagement. The findings make a recommendation to managers who would wish to establish long term brand equity in the responsible and touchable market through integrating sustainability commitments in the meaningful customer experience.